Pyrometer with video monitoring of measurement area - V. A. Zakharenko; D. G. Lobov; A. G. Shkayev; A. A. Valke (Омский научный вестник)
A pyrometer with non-parallel sighting is developed, which allows simultaneously with temperature measurement to perform video surveillance of the control object. Pyrometer has optically connected lens, signal meter, thermostat in which radiation receiver is placed, and video camera. The front surface of the thermostat is polished, directed at an angle of 45 ° to the optical axis of the lens and has a hole that acts as a field diaphragm. Video camera is directed to polished surface of thermostat perpendicular to optical axis of lens. Pyrometer operation, its design and functional diagram are described.